Pola Kemitraan Ayam Ras Pedaging Pola Kemitraan Ayam Ras Pedaging dan Pengaruh Karakteristik Peternak, Pendapatan serta Pelayanan Perusahaan terhadap Loyalitas Kerjasama (Studi di PT. Semesta Mitra Sejahtera, Kabupaten Tulungagung) - Onny Nurihayanti (Manajemen Agribisnis: Jurnal Agribisnis, 2022)
Poultry business development is a reliable business, providing a significant increase in income, opening up employment opportunities, a source of fulfilling community nutrition and supporting the industrial sector. General Director of PKH (2020) said that East Java's chicken meat production in 2018 was 480,309.46 tons, in 2019 it was 506,731.16 tons and in 2020 it was as high as 474,868.84 tons. Economic conditions will foster competition among business actors, especially for large-scale business actors, the small farmers will suffer even more due to various limitations. The solution that can provide a solution to the problem of developing a poultry business, especially broilers, is through a partnership pattern. This study aims to determine the effect of breeder characteristics (X1), income (X2) and company services (X3) on loyalty cooperation (Y) partnership pattern at PT. Semesta Mitra Sejahtera, Tulungagung. This type of research is a survey research using 60 samples. Collecting data using a questionnaire method with a Likert scale, observation and interviews. Data analysis using SPSS 24 includes classical assumption test and multiple linear regression analysis to test the hypothesis. Resulting of the regression analysis show the function equation Y = 0.159 + 0.143X1 + 0.003X2 + 0.844X3+e has a coefficient of determination (R2) of 0.822, means that cooperation loyalty is influenced by breeder characteristics, income and company services of 82.2%. The result of hypothesis test are stated: an influence between the characteristics of breeders on cooperation loyalty (H1 is accepted), nothing effect between breeders' income on cooperation loyalty (H2 is rejected) and influence between company services on cooperation loyalty (H3 is accepted).